Increasing women's empowerment: Implications for family welfare - Ambler, Kate; Jones, Kelly M.; O'Sullivan, Michael (Institute of Labor Economics, 2021)
Increasing women's empowerment is a key objective of many development programs, both as a principal goal and as a path to economic development. We propose and test a novel economic intervention that relies on intra-household transfers of productive assets to increase women's empowerment among sugar farmers in Uganda. We document that this intervention increases women's access to resources and agency by a substantial amount. In contrast, a behavior change intervention (training) increases empowerment through agency and achievements, with no impact on access to resources. We use these interventions to test the widely held (but weakly supported) assumption that empowering women generates improvements in child welfare. We find that, contrary to studies examining extra-household transfers, these interventions do not shift food security, health, or educational outcomes. They do, however, improve life satisfaction both for women and their husbands.